Comparative Proteomic Analysis of Visceral Adipose Tissue in Morbidly Obese and Normal Weight Chinese Women - Chen Shang; Wei Sun; Chunlin Wang; Xiangqing Wang; Huijuan Zhu; Linjie Wang; Hongbo Yang; Xue Wang; Fengying Gong; Hui Pan (International Journal of Endocrinology)
Objective. Visceral adipose tissue (VAT) plays a central role in the balance of energy metabolism. The objective of this study was to investigate the differentially expressed proteins in VAT between morbidly obese (BMI >35 kg/m2) and normal weight Chinese women. Method. Nine morbidly obese women and 8 normal weight women as controls were enrolled. Abdominal VAT was excised and analyzed by label-free one-dimensional liquid chromatography tandem mass spectrometry (1D-LC-MS/MS). Differentially expressed VAT proteins were further analyzed with Gene Ontology (GO) analysis and Ingenuity Pathway Analysis (IPA). Masson’s trichrome staining and CD68 immunohistochemical staining of VAT were conducted in all subjects. Result. A total of 124 differentially expressed proteins were found with a ≥2-fold difference. Forty-one proteins were upregulated, and 83 proteins were downregulated in obese individuals. These altered VAT proteins were involved in the attenuation of the liver X receptor/retinoid X receptor (LXR/RXR) signaling pathway and the activation of the acute-phase response process. Three proteins (ACSL1, HADH, and UCHL1) were validated by western blotting using the same set of VAT samples from 6 morbidly obese and 7 normal weight patients, and the results indicated that the magnitude and direction of the protein changes were in accordance with the proteomic analysis. Masson’s trichrome staining and CD68 immunohistochemical staining demonstrated that there was much more collagen fiber deposition and CD68-positive macrophages in the VAT of morbidly obese patients, suggesting extensive fiber deposition and macrophage infiltration. Conclusion. A number of differentially expressed proteins were identified in VAT between morbidly obese and normal weight Chinese females. These differential proteins could be potential candidates in addressing the role of VAT in the development of obesity.